TABLE TALK: Impact of intergenerational food transmission on the nutritional environment and strategies for the prevention of eating disorders - Meek, Kathleen Malone (My University, 2025)
This report examines the role of intergenerational food transmission in the prevention of eating disorders, emphasizing the influence of early feeding practices and family food environments on long-term relationships with food and body image. As rates of disordered eating continue to rise, this research highlights protective strategies rooted in nutrition science and developmental psychology, including shared family meals, responsive feeding using Satter’s Division of Responsibility, and parental modeling of intuitive eating. Through a comprehensive review of current literature, this report explores how food behaviors, attitudes, and language are passed down within families, often shaping a child’s internal regulation and self-perception. Particular attention is given to the impacts of weight-focused talk, food moralization, and restrictive feeding on emotional and physical health outcomes. Findings suggest that fostering autonomy at the table, eliminating shame-based messaging, and creating emotionally supportive food environments can reduce the risk of disordered eating and promote a lifelong, positive relationship with food. The research calls for more inclusive, longitudinal studies across diverse family structures, cultures, and socioeconomic contexts to better understand and apply these findings. This work positions food not just as sustenance, but as a vehicle for connection, identity, and emotional well-being. The research offers a framework for prevention that begins in the home and has the potential to shift generational narratives around eating and body trust.
Keywords: Intergenerational food transmission; Parental modeling; Disordered eating prevention; Division of Responsibility; Responsive feeding; Fat talk; Body image; Family meals